2018
DOI: 10.2147/ahmt.s173115
|View full text |Cite
|
Sign up to set email alerts
|

Online information and support needs of young people with cancer: a participatory action research study

Abstract: PurposeThe Internet is a fully integrated part of young people’s life and it is pivotal that online resources are developed to maximize the potential of the Internet to support those living with and beyond cancer. We sought to understand how young people with a cancer diagnosis use the Internet and to what extent information and support needs are met by existing online resources.Patients and methodsThis was a participatory action research study involving 21 young people participating in workshops and individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 21 publications
1
40
0
1
Order By: Relevance
“…A common theme among the selected records (n = 20) was that AYA are a unique group with unique information needs. 18,22,[34][35][36][37][38][39]42,43,[47][48][49][50][51][52][53][54][55][56][57] This ''uniqueness'' was attributed to numerous factors, such as the intrinsic developmental specificities of AYA patients and the rarity of what AYA are experiencing compared to their peers.…”
Section: General Features Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A common theme among the selected records (n = 20) was that AYA are a unique group with unique information needs. 18,22,[34][35][36][37][38][39]42,43,[47][48][49][50][51][52][53][54][55][56][57] This ''uniqueness'' was attributed to numerous factors, such as the intrinsic developmental specificities of AYA patients and the rarity of what AYA are experiencing compared to their peers.…”
Section: General Features Of the Included Studiesmentioning
confidence: 99%
“…35,38,43,49,51 They reported that most AYA with cancer look for factual online information on diagnosis, treatments, symptoms, and side effects. However, the desire to access cancer information varies depending on the phase of the cancer timeline 38,49 : When on treatment, AYA prefer to receive information on cancer management from their treatment team and tend to use internet and social media predominantly for entertainmentrelated purposes and to stay in contact with family and friends. AYA who have completed their treatment, however, more often actively seek practical information on issues such as body image, fertility, fear of recurrence, nutrition, health insurance, and financial support.…”
Section: General Features Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition at the end of active treatment into life after cancer often generates feelings of anxiety, fear and uncertainty for patients and families (Nathan et al, 2011). It has been reported that AYA can feel unprepared for life after treatment and experience new concerns around maintaining health and wellness when cancer treatment ends (Fern et al, 2013;Lea et al, 2018;Nathan et al, 2011;Thompson, Palmer, & Dyson, 2009). It has been proposed that AYA should have "access to resources and/or referral information that can help them reintegrate back into normal society" (Thompson et al, 2009, p. 210).…”
mentioning
confidence: 99%
“…Récemment, on a viserà mieux comprendre l'expérience des jeunes adultes souffrant d'un cancer avancé et la manière d'optimiser leurs efforts d'adaptation psychosociale en faisant appel aux ressources personnelles et aux services en santé (DePauw et al, 2019;Cheung et Zebrack, 2017;Lea et al, 2018;Leuteritz et al, 2017;Quinn et al, 2015;Warner et al, 2018;Zebrack et al, 2013). Le sentiment d'habilitation est bien sûr inhérent à ces processus.…”
unclassified